Promotion of Biodiversity Conservation and Local Livelihoods in Buxa Tiger Reserve: Challenges and Opportunities - Das, Uttam; Behera, Bhagirath (Journal of Rural Development, 2023)
The present paper attempts to outline the emerging twin challenges of biodiversity conservation and the promotion of local livelihood opportunities for local people residing in and around the Buxa Tiger Reserve (BTR) in the Indian State of West Bengal. The study is based on a comprehensive review of the existing literature, secondary data collected from various government reports, and interaction with local forest dwellers in and around the nature park. The study finds that although the Buxa Tiger Reserve houses some of the critically threatened species, both flora and fauna, it is under severe pressure from both natural and anthropogenic factors. The natural factors that are threatening the nature park include climate change-induced water scarcity, frequent droughts and erratic rainfall. This has also brought about livelihood insecurity among local inhabitants, which has resulted in human-wildlife conflicts, illegal and rampant wildlife poaching, fragmented landscapes due to encroachment, deforestation, forest fire, the conflict between the forest department and local people, and others. Hence, sustainable use and management of park resources require both effective conservation measures and local livelihood strategies. Efforts should be made for adopting participatory biodiversity conservation strategies in which both park authority and local people work collectively towards achieving desired conservation and livelihood outcomes.